Too Old to Punish? Reconsidering Rechterlijk Pardons for Elderly Offenders - Angga Angga; Muhammad Azil Maskur; Ridwan Arifin; Muhammad Nuruddin Ahmad Zaki (Jurnal Hukum Replik, 2025)
TheÂ introduction of rechterlijk pardon (judicial pardon) within the reformed Criminal Code represents a significant legislative shift toward mitigating the punitive burden on elderly offenders. This study explores the intersection of judicial leniency and restorative justice, evaluating how the suspension of imprisonment can facilitate the rehabilitation of the perpetrator while addressing the victim's needs. Utilizing a normative juridical method with a qualitative approach, the research analyzes primary legal instrumentsâ€”specifically the new Indonesian Criminal Codeâ€”alongside secondary legal literature and comparative jurisprudence. Data validity is ensured through theoretical and source triangulation. The findings indicate that while the current legal framework explicitly permits judicial pardon for offenders aged 75 and over, a gap exists regarding those under this threshold who suffer from age-related physical and psychological decline. The study argues that the application of rechterlijk pardon should not rely solely on chronological age but should integrate restorative justice principles to achieve â€œwin-winâ€ outcomes. This research contributes to the discourse on geriatric criminology and legislative reform by proposing a more nuanced, health-based criteria for judicial discharge. It offers a framework for judges to balance statutory requirements with the human rights of elderly defendants, advocating for a restorative model that moves beyond mere incarceration toward social reintegration.